Stem Cell Therapy to Treat Diabetes Mellitus (The Review of Diabetic Studies, 2023)
Transplantation of pancreatic islets offers a direct treatment for type 1 diabetes and in some cases, insulin-dependent type 2 diabetes. However, its widespread use is hampered by a shortage of donor organs. Many extant studies have focused on deriving β-cell progenitors from pancreas and pluripotent stem cells. Efforts to generate β-cells in vitro will help elucidate the mechanisms of β-cell formation and thus provide a versatile in vivo system to evaluate the therapeutic potential of these cells to treat diabetes. Various successful experiments using β-cells in animal models have generated extensive interest in using human embryonic stem cells to restore normoglycemia in diabetic patients. While new techniques are continually unveiled, the success of β-cell generation rests upon successful manipulation of culture conditions and the induction of key regulatory genes implicated in pancreas development. In this review, we compare successfully conducted protocols, highlight essential steps and identify some of the remarkable shortfalls common to these methods. In addition, we discuss recent advancements in the derivation of patient-specific pluripotent stem cells that may facilitate the use of autologous β-cells in stem cell therapy.